The Effect of Listening to Murottal Al-Quran on Reducing Academic Anxiety in Students - Dwi Fitria Sari; Boti Andika; Prillya Elmadisa (Educate : Journal of Education and Learning, 2025)
Academic worry is something commonly experienced by many people.One of the frequently used ways to overcome academic worry is to listento Murottal Al-Quran. Study This aims to evaluate how effective listeningto Murottal Al-Quran is in reducing anxiety among students in the city ofPalembang. Research methods This uses a design experiment withtechnique taking random samples One pretest-posttest group. A total of15 students in the city of Palembang became the subjects of this study.Anxiety scale from Isthifha (2011) is used in this study. Research resultsshow that therapeutic listening to Murottal Al-Quran is not valid and hasa significant impact in reducing academic worry in students.